Quality characteristics of reduced fat emulsion-type chicken sausages using chicken skin and wheat fiber mixture as fat replacer. (29th January 2019) - Choe, Juhui; Kim, Hack-Youn
ABSTRACT: This study identified the suitability of chicken skin and wheat fiber mixture (CSFM ) as an optimal fat replacer and its addition levels in reduced fat emulsion-type sausages, also paying heed to quality characteristics. Two CSFM types [CSFM-1 and CSFM-2 (chicken skin:ice:wheat fiber = 5:3:2 or 3:5:2, respectively)] were added at 0, 5, 10, 15, and 20% (w/w) as fat replacer. As the addition level increased, higher moisture and lower fat content were observed in the sausage samples without protein content loss ( P < 0.05). Emulsion stability and pH were not significantly affected. Replacement with CSFM-2 at levels exceeding 15% significantly reduced cooking yield. While partial change in instrumental color was observed depending on replacer type and addition level, the panel did not detect the same. Hardness increased significantly with increasing addition levels. The panel detected decreased tenderness at 20% and 10 to 20% CSFM-1 and CSFM-2, respectively ( P < 0.05). Twenty percent CSFM-1 and >10% CSFM-2 additions induced significant decrease in overall acceptability compared to the control. Thus, CSFM can be used as a fat replacer in reduced fat emulsion-type sausages at addition levels of 15% CSFM-1 (7.5% chicken skin, 4.5% water, and 3% wheat fiber based on total weight of meat batter) or 5% CSFM-2 (1.5% chicken skin, 2.5% water, and 1% wheat fiber based on total weight of meat batter).